Comparison of Phytochemical Content and Toxicity of n-hexana Extracts and Fractions of Padina australis - Panjaitan, Riong Seulina; Farida, Herni (Department of Chemical Education Faculty of Teacher Training and Education Universitas Su, 2023)
Padina australis is a brown macroalgae that is abundant in Indonesian coastal waters. It is known to contain bioactive compounds such as alkaloids, flavonoids, steroids, saponins, and tannins. This research aims to produce and determine the best extraction technique to increase the % yield and test the toxicity of the methanol extract and the n-hexane fraction of Padina australis. This study began with macroalgae sampling, determination, extraction (maceration and Ultrasound-Assisted Extraction (UAE)), phytochemical screening, liquid-liquid fractionation, thin layer chromatography, and BSLT (Brine Shrimp Lethality Test) toxicity testing. According to the research results, it is known that the UAE method provides the highest % yield of methanol extract at 10.86% compared to the maceration method, namely 4.76%. Furthermore, there was no difference in the phytochemical content of the two extraction methods. Meanwhile, there are differences in the phytochemical content of the n-hexane fraction, namely that the maceration method contains steroids, and the UAE contains steroids and saponins. Then, the toxicity test for the methanol extract obtained the highest LC50 value for the UAE method at 352.508 ppm, while for the n-hexane fraction, the highest LC50 value was 54.99 ppm. The methanol extract and n-hexane fraction in the toxicity test were included in the very toxic and toxic categories. The benefit of this research is to provide information about the comparison of the two extraction methods and toxicity tests of the methanol extract and n-hexane fraction of Padina australis.